Modern methods of treatment of locally-advanced and recurrent basal cell carcinoma of the head and neck with using signal pathway inhibitor Hedgehog: сlinical cases - A. P. Polyakov; E. Iu. Vasileva; А. А. Polyakov (Опухоли головы и шеи)
The study objective is to analyze the efficacy of a hedgehog signaling pathway inhibitor in locally advanced and recurrent basal-cell carcinoma (BCC) of the head and neck.Materials and methods. We compared the information from international clinical guidelines and two clinical trials (ERIVANCE and STEVIE). We also provide two case reports of a hedgehog signaling pathway inhibitor (vismodegib) use.Results. In the ERIVANCE trial, the objective response rate was 48.5 % in patients with metastatic BCC and 60.3 % in patients with locally advanced BCC. The median progression-free survival was 9.3 and 12.9 months in participants with metastatic and locally advanced BCC respectively. The overall survival reached 33.4 months in patients with metastatic BCC and was not reached in patients with inoperable BCC. According to the results of the STEVIE  trial, vismodegib ensured disease control in 93 % of patients with locally advanced BCC and 72 % of patients with metastatic BCC. The median progression-free survival was 24.5 and 13.1 months in participants with locally advanced and metastatic BCC respectively. The majority of vismodegib-realted adverse events in both ERIVANCE BCC and STEVIE trials were grade I/II adverse events. In the two clinical trials, vismodegib at a dose of 150 mg per day during 3 months caused visual reduction of the bone destruction focus, which was confirmed by computed tomography. Patients were recommended to continue therapy with vismodegib.Conclusion. Until recently, there were no treatment standards for late-stage BCC. Currently, hedgehog signaling pathway inhibitors, such as vismodegib, can be considered as a method of choice for patients with inoperable and metastatic BCC, since this therapy demonstrated high efficacy.